PENGARUH DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI INKLUSIF MELALUI KETIMPAGAN PENDAPATAN DI SUMATERA BARAT - Nahda Fidarsih; Novya Zulva Riani (Universitas Negeri Padang, 2025)
This research aims to analyze the influence of balancing funds on inclusive economic growth in West Sumatra from 2018 to 2023. The approach used is quantitative with panel data regression methods, utilizing secondary data from the Central Statistics Agency (BPS) and Ministry of Finance data. The variables studied include General Allocation Funds (DAU), Special Allocation Funds (DAK), and Profit Sharing Funds (DBH) and their impact on inclusive economic growth in overcoming income inequality in 19 districts/cities in the Sumatra region West. Simultaneous estimation results show that balancing funds have a significant effect on inclusive economic growth through income inequality. The results of this research highlight the importance of government policy in equalizing balancing funds so that they are felt by all levels of society and can reduce income inequality.